Dignifying Children through Inclusive Children’s Literature - Kristanti, Fransisca (Journal of Language and Literature, 2016)
Children with disabilities are often considered less capable than those without disabilities. In Indonesian children’s literature, disability is under-represented and the need to start representing disability in Indonesian children’s literature is pressing. Inclusive books imposing on the development of empathy leads to actions in dignifying children of all types, with or without disabilities. Some inclusive children’s literature worldwide set good examples of dignifying children. This paper tries to elaborate the urgency of having accessible inclusive children’s literature in Indonesia by collecting and presenting examples of inclusive children’s literature around the world which represents disabilities as diversities in society.